Choosing the Optimal Segmentation Technique to Understand Tourist Behaviour. (January 2023) - McKercher, Bob; Tolkach, Denis; Eka Mahadewi, Ni Made; Byomantara, Dewa Gde Ngurah
This study compares and contrasts five different segmentation techniques to determine which one(s) best describe behaviour among independent tourists who visited Bali, Indonesia. The five techniques included geographic, demographic, behavioural and motivation segmentation, plus a hybrid technique that included geographic, demographic and behavioural variables. The study revealed geographic segmentation proved to be the most efficacious, with motivation segmentation least reliable. However, the authors caution that the preferred segmentation technique depends on the objectives of the study, with each method adopted serving a specific purpose.